Optimization of Utilization of E-Commerce on Halal Products in Indonesia - Utami, Pertiwi; Asriani (Eastern Journal of Economics and Finance, 2019)
Consumption of halal products in Indonesia continues to increase. In 2019, it is predicted, the e-commerce market in Indonesia will increase to 31% or equivalent to US 3.8 billion. Spike Choo, coutry director of Frost & Sullivan Indonesia stated that, "Poor infrastructure conditions and low access to financial institutions will be challenges for the e-commerce industry in Indonesia." E-commerce halal products emerged as an alternative medium for buying and selling halal products. Responding to the phenomenon that occurs, optimizing the use of e-commerce is needed to face challenges and increase interest in halal products. A study of literature with a review of Islamic law regarding the use of e-commerce is done to find the right strategy as a step to optimize halal products. We find that in order to achieve the optimization of e-commerce halal products, the conditions that must be met are the fulfillment of halal-guaranteed product quality, the implications of resource empowerment, management of Islamic business, Islamic business ethics, Muslim consumer behavior and business capital.